2017
DOI: 10.5194/acp-17-117-2017
|View full text |Cite
|
Sign up to set email alerts
|

Argon offline-AMS source apportionment of organic aerosol over yearly cycles for an urban, rural, and marine site in northern Europe

Abstract: International audienc

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 76 publications
8
51
0
Order By: Relevance
“…4e and f), and the relation to markers (Fig. 5c and d) of the two factors are in agreement with those from earlier work at other locations, including Zürich (Daellenbach et al, 2016), Payerne , and Lithuania (Bozzetti et al, 2017a). This OOA separation appears to be typical for PMF analysis of long-term, low-timeresolution OA mass spectra of filter samples.…”
Section: Interpretation Of Pmf Factorssupporting
confidence: 78%
See 2 more Smart Citations
“…4e and f), and the relation to markers (Fig. 5c and d) of the two factors are in agreement with those from earlier work at other locations, including Zürich (Daellenbach et al, 2016), Payerne , and Lithuania (Bozzetti et al, 2017a). This OOA separation appears to be typical for PMF analysis of long-term, low-timeresolution OA mass spectra of filter samples.…”
Section: Interpretation Of Pmf Factorssupporting
confidence: 78%
“…The measurement blank was subtracted from the sample spectra. In a previous study, it has been shown that the measurement blank is comparable to the organic blanks obtained from the nebulization of NH 4 NO 3 (Bozzetti et al, 2017a …”
Section: Offline Ams Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We note that while the assessment of the uncertainties related to the O : C measurements by the HR-ToF-AMS is not straightforward, a distinction should be made between measurement precision and accuracy. We do not expect the accuracy of the O : C ratios determined by the HR-ToF-AMS to be less than ∼ 20 % (Aiken et al, 2008;Pieber et al, 2016;Canagaratna et al, 2015;Bozzetti et al, 2017). For example, the use of a more recent parameterization would yield higher O : C values (by 18 %) and the O : C ratios reported here may be regarded as the lowest estimates.…”
Section: Experimental Set-up and Instrumentationmentioning
confidence: 67%
“…The recent utilization of the AMS for the offline analysis of ambient filter samples has significantly broadened the spatial and temporal scales accessible to high-resolution AMS measurements (Daellenbach et al, 2017;Bozzetti et al, 2017a, b). In addition, the technique enables measurement of aerosol composition outside the normal size transmission window of the AMS; the standard AMS can measure up to only 1 µm, or ∼ 2.5 µm with a newly developed aerodynamic lens (Williams et al, 2013;Elser et al, 2016).…”
Section: Introductionmentioning
confidence: 99%